RISK FACTORS FOR THE DEVELOPMENT OF LOCAL RECURRENCES OF INVASIVE BREAST CANCER - Sultonova Lola Jahonqulovna; Sokhibova Ziyoda Rakhmonovna; Makhmudova Guljamol Fazliddinovna; Barotova Shahnoza Bakhodirovna (Galaxy International Interdisciplinary Research Journal, 2021)
The influence of biological characteristics and receptor status of the primary tumor on the risk of local recurrence of breast cancer was analyzed. Factors that increase the frequency of ipsilateral relapses have been identified: preserved menstrual function, metastases in regional lymph nodes.